Trichological analysis of guard hairs of Mus musculus, Rattus rattus e Rattus norvegicus (Rodentia: Muridae) applied to research and identification in food - Iara Aquino, Cinthia; Quadros, Juliana (Instituto Nacional de Controle de Qualidade em Saúde, 2022)
Introduction: Rodents are among the most important pests in the world and when these individuals or their fur are found in food, they are considered foreign matter indicative of health risk. On the other hand, the presence of human and other mammalian hair is considered indicative of failures in good practices. Thus, the characterization of the hairof synanthropic rodents and its differentiation from other mammal species are relevant and necessary. Objective: To characterize the microstructural patterns of guard hairs of the three main species of rodents that infest food storage environments and to present a proposal for a protocol for the trichological analysis of isolated hairs. Method: Hair samples were plucked from collected specimens of the rodent species Mus musculus, Rattus rattus and Rattus norvegicus. Intact guard hairs were selected for the preparation of slides for observation of the microstructure. In total, 20 guard hairs were analyzed for the characterization of medullary patterns and 91 guard hair cuticular impressions were examined for the characterization of cuticularpatterns. Results: It was observed that M. musculus presented alveolar medulla and losangic cuticle with variations in the shape and size of the scales. R. rattus and R. norvegicus presented reticulated medulla and losangic cuticle, also with variations. A protocol with an identification fluxogram was presented for the analysis of the studied hairs. Conclusions: The hairs of the studied synanthropic rodent species can be differentiated from other mammalian species of health interest by the presence of alveolar and reticulated medullary patterns in the guard hair shield. For the studied species, only the medullary pattern of the guard hair shield confers a diagnostic character. Introdução: Roedores estão entre as mais importantes pragas do mundo e, quando estes indivíduos ou seus pelos são encontrados nos alimentos, são considerados matérias estranhas indicativas de risco à saúde. Por outro lado, a presença de pelos humanos e dos ...